Application of the Problem Based Learning (PBL) Model Assisted by Canva Media to Increase Interest in History Subjects for Class X.9 SMA Negeri 5 Medan - Ulfa, Riska; Nasution, Abd Haris; Nasution, Sovianur (CV. Rayyan Dwi Bharata, 2024)
This research aims to increase students' interest in learning in the subject of History by implementing the Problem Based Learning (PBL) learning model assisted by Canva media. The research was conducted in class X.9 of SMA Negeri 5 Medan. The method used is classroom action research (PTK) with two cycles. Each cycle consists of planning, implementation, observation and reflection stages. Data was obtained through observation, interviews, and student learning interest questionnaires. The research results show that the application of the PBL learning model assisted by Canva media is able to increase students' interest in learning significantly. Using Canva media in the learning process makes the material more interesting and easy to understand, so that students are more actively involved in learning. This research suggests implementing the PBL learning model with the support of digital media such as Canva as an effective strategy in increasing students' interest in learning, especially in History subjects.